Telaah Social Capital Pada Wilayah Perbatasan Kabupaten Aceh Tamiang, Provinsi Aceh - Zaki Fuad Khalil; Muhammad Zulhilmi; Hafiizh Maulana (SI-MEN, 2018)
The border area is identical with the condition of the community that a high level of diversity. Aceh Tamiang district is one of the border areas between North Sumatra and Aceh Province. This study aims to examine the variables that become potential social capital in Aceh Tamiang district, to further be traced the extent to which the influence of social variables on economic performance. The methodology used in this research is Linear Multiple Regression analysis, which consists of 4 structural equations including income, consumption, investment and Zakat model. Variable social capital that can strengthen the economic dimension in Aceh Tamiang Regency is access to education, the number of community civil society, and dependency ratio. The ability to access education, increasing the number of community civil society, has a significant effect on income per capita and consumption levels. The strengthening of a social capital variable in Aceh Tamiang Regency is specifically able to strengthen the acceptance of zakat with strong determinant between education and community organizing institution to zakat acceptance